Discrete and continuous dynamical systems: preface - Pinho, Maria do Rosário (2012)
These preface words, quoted in Francis Clarke's 1983 book, stroke a sensitive chord and set the tone for a vision fueling the construction of an extremely rich body of intertwined developments in nonsmooth analysis, optimization and control by a carefully networked community. This special issue comprises post-conference articles from a selection of works presented at the Workshop on Control, Nonsmooth Analysis and Optimization, held in Porto, Portugal in May 2009. The workshop was part of the celebrations of the 60th birthday of Francis Clarke and Richard B. Vinter.